2021
DOI: 10.1542/peds.2020-042069
|View full text |Cite
|
Sign up to set email alerts
|

Central Venous Catheter Salvage in Ambulatory Central Line–Associated Bloodstream Infections

Abstract: BACKGROUND Guidelines for treatment of central line–associated bloodstream infection (CLABSI) recommend removing central venous catheters (CVCs) in many cases. Clinicians must balance these recommendations with the difficulty of obtaining alternate access and subjecting patients to additional procedures. In this study, we evaluated CVC salvage in pediatric patients with ambulatory CLABSI and associated risk factors for treatment failure. METHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 12 publications
1
14
1
Order By: Relevance
“…The issue of whether the CVC should be removed as early as possible after the occurrence of sepsis has been the topic of debate as most critically ill patients need the CVC for antibiotic administration and fluid supplementation. Although there have been multicenter studies that did not reach a conclusion on the importance of early CVC removal to the outcomes [ 31 , 32 , 33 ], we did find that delayed CVC removal in neonates with candidemia was independently associated with final in-hospital mortality. This can probably be explained by these patients being more likely to have persistent candidemia and/or breakthrough candidemia, which is associated with final adverse outcomes [ 34 , 35 ].…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The issue of whether the CVC should be removed as early as possible after the occurrence of sepsis has been the topic of debate as most critically ill patients need the CVC for antibiotic administration and fluid supplementation. Although there have been multicenter studies that did not reach a conclusion on the importance of early CVC removal to the outcomes [ 31 , 32 , 33 ], we did find that delayed CVC removal in neonates with candidemia was independently associated with final in-hospital mortality. This can probably be explained by these patients being more likely to have persistent candidemia and/or breakthrough candidemia, which is associated with final adverse outcomes [ 34 , 35 ].…”
Section: Discussioncontrasting
confidence: 81%
“…However, in cases when the catheter is not the source of sepsis, it deserves a prospective, randomized controlled trial to document whether prompt catheter removal contributes significantly to the outcomes as it is often difficult to reinsert the CVC during the critically ill period. Because of different study designs, cohort selections, and perhaps the bias of illness severity, previous studies failed to have undebatable conclusions [ 31 , 32 , 33 , 36 ]. Nevertheless, we suggest that CVC removal at earliest stage of sepsis should be considered for neonates with candidemia, based on our study result and the current guidelines [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ford et al found no difference in the rate of salvage attempts for those with fungal infections versus other infection types. Similar to our patient population, they had a significantly lower rate of successful salvage for patients with fungal infections (11%) compared to other infection types (77.3%) 10 . The use of ethanol locks may help increase the success of line salvage in the setting of fungal infections 17 .…”
Section: Discussionsupporting
confidence: 61%
“…Our relatively homogenous patient population of patients with IF may also have contributed to our higher successful salvage rate compared to other studies. 10,13 The types of infections treated also likely contributes to the salvage rates, as many studies looked at just one infection type such as Staphylococcus aureus. 11,12 The IDSA suggests removal for all infections with S. aureus, Pseudomonas aeruginosa, Mycobacterium, polymicrobial infections, and Candida and that line salvage should only be attempted in "extenuating circumstances."…”
Section: Length Of Stay and Complicationsmentioning
confidence: 99%
See 1 more Smart Citation